Effect of Copper (Ii) Biosorption over Light Metal Cation Desorption in the Surface of Macrocystis Pyrifera Biomass - Pizarro-Konczak, J; Ortiz-Calderon, C (Elsevier Ltd, 2020)
We study the effect of Cu(II) biosorption on the displacement of intrinsic light metal cations of the surface of the biomass of the brown macroalgae Macrocystis pyrifera. Batch methods and non-linearized kinetic models show chemisorption with a fast reach to equilibrium, represented by a pseudo-second order kinetic model. The non-linear Langmuir isotherm model fits right to the data with a value of maximum capacity of 1.251 mmol g-1 at pH 5. The light metal cations desorption induced by Cu(II) biosorption, show an increase in the desorption of alkali-terrous cations when more Cu(II) is available, especially the desorption of Ca cations. The infrared analysis shows that the functional groups amine, carboxylate, hydroxyl and sulphonate are the main moieties in this biomass. We observed changes in surface texture due to the desorption of light metal cations, and a rearrangement by an apparent increase in fibrillar crosslinking due to the Cu(II) biosorption. The results of the present work show that the cation exchange with Ca and Mg is the primary mechanism in the overall Cu(II) biosorption on M. pyrifera biomass, representing a 56 % of the total of Cu(II) bound. © 2020 Elsevier Ltd.